Review of the subtribe Gyrophaenina Kraatz, 1856 (Coleoptera: Staphylinidae: Aleocharinae: Homalotini) of Kunashir Island, with notes on species of Far Eastern Russia - Enushchenko, Ilya V.; Makarov, Kirill V.; Shavrin, Alexey V. (Zootaxa, 2024)
Taxonomic, diagnostic and faunistic data for 30 species of three genera (Agaricochara Kraatz, 1856 (one species), Gyrophaena Mannerheim, 1830 (27 species) and Sternotropa Cameron, 1920 (two species) of the subtribe Gyrophaenina Kraatz, 1856 of Kunashir Island (Kuril Islands, Far Eastern Russia) are provided. All these species are recorded from Kunashir and Kuril Islands, and the genera Agaricochara and Sternotropa from Russia, for the first time. Eleven new species are described and illustrated: Agaricochara verrucosa Enushchenko, sp. nov., G. (s.str.) ainuorum Enushchenko, sp. nov., G. (s.str.) rama Enushchenko, sp. nov., G. (s.str.) robertopacei Enushchenko, sp. nov., G. (s.str.) semenovi Enushchenko, sp. nov., G. (s.str.) volkeri Enushchenko, sp. nov., Sternotropa aiaia Enushchenko, sp. nov. and S. kamuy Enushchenko, sp. nov. from Kunashir Island, G. (s.str.) kerzhneri Enushchenko, sp. nov. and G. (s.str.) melanoceta Enushchenko, sp. nov. from Maritime Province and Kunashir Island, and G. (s.str.) rebrievi Enushchenko, sp. nov. from Khabarovsk Territory, Maritime Province and Kunashir Island. Three species of Gyrophaena are redescribed and illustrated: G. (s.str.) anastasiarum Glotov, 2022, G. (s.str.) bernhaueri Jakobson, 1909, and G. (s.str.) plutenkoi Glotov, 2014. Besides that, 18 species of the genus Gyrophaena were recorded from the mainland provinces of Far Eastern Russia, including description of G. (s.str.) frolovi Enushchenko, sp. nov. from Amur Area, Khabarovsk Territory and Maritime Province. Based on the study of the types and additional material, the following new synonymies are established: G. (s.str.) bihamata Thomson, 1867 = G. guttula Pace, 2010 syn. nov., G. (s.str.) cariniventris Cameron, 1933 = G. monospina Pace, 2003 syn. nov., G. (s.str.) gonggamontis Pace, 2010 = G. (s.str.) aedugena Enushchenko, 2011 syn. nov., G. (s.str.) harmandi Fauvel, 1901 = G. alexandrovi Bernhauer, 1939 syn. nov., G. (s.str.) taeniae Pace, 2007 = G. ashei Kim & Ahn, 2009 syn. nov., G. (s.str.) permixta Pace, 2003 = G. bifurcata Assing, 2005 syn. nov., and G. (s.str.) zhagaensis Pace, 2003 = G. peniculi Pace, 2007 syn. nov. Habitus, aedeagi, apical abdominal segments and spermathecae of several little-known species of Gyrophaenina are illustrated. A key to species of the bihamata group of Gyrophaena is presented. Several species are recorded for the first time from certain regions: G. (s.str.) bernhaueri, G. (s.str.) cariniventris, G. (s.str.) deprehendens Pace, 2007, G. (s.str.) discoidea Pace, 2003, G. (s.str.) harmandi, G. (s.str.) pasniki Assing, 2005, G. (s.str.) permixta, G. (s.str.) schuelkei Pace, 2003, G. (s.str.) taeniae, G. (s.str.) taiwanova Pace, 2007, G. (s.str.) torta Assing, 2005, G. (s.str.) triquetra Weise, 1877, G. (s.str.) williamsi A. Strand, 1935, G.(s.str.) yotsudeba Cameron, 1933, G. (s.str.) zhagaensis and G. (Phaenogyra) tetracuspidata Assing, 2005 from Russia, G. (s.str.) joyi Wendeler, 1924, G. (s.str.) obsoleta Ganglbauer, 1895, G. (s.str.) orientalis A. Strand, 1938, G. (s.str.) pseudonana A. Strand, 1939, G. (s.str.) pulchella Heer, 1839 and G. (Phaenogyra) strictula (Erichson, 1839) from Far Eastern Russia, G.(s.str.) gonggamontis from Zabaykalsky Krai, Jewish Autonomous Area, Sakhalin Area and Mongolia, G. (s.str.) rugipennis Mulsant & Rey, 1861 from Zabaykalsky Krai, Khabarovsk Territory and Sakhalin Area, G. (s.str.) congrua Erichson, 1837 from Amur Area, Khabarovsk Territory and Sakhalin Area, G. (s.str.) kaunshanchiensis Pace, 2007 from Khabarovsk Territory and Sakhalin Area, G. (s.str.) pseudonitidula Semenov, 2015 from Sverdlovsk, Irkutsk and Amur areas, G. (s.str.) affinis Mannerheim, 1830, G. (s.str.) congrua Erichson, 1837 and G. (s.str.) poweri Crotch, 1867 from Amur Area and Khabarovsk Territory, and G. (s.str.) anastasiarum and G. (s.str.) plutenkoi from Sakhalin Area. In general, based on the published and new data, 53 species of four genera of Gyrophaenina are known from Far Eastern Russia: Agaricochara (one species), Encephalus Stephens, 1832 (one species), Gyrophaena (49 species) and Sternotropa (two species). The composition of the fauna and zoogeographic and bionomical features of Gyrophaenina of Kunashir Island and Far Eastern Russia are briefly discussed. Besides that, we noted the richness of the fauna of Kunashir in comparison with adjacent territories.